(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
This research had as its main objective to analyze the impact of taxation on the result of the profitability of the major investments and financial investments offered in the domestic financial market. For this a descriptive, documental and quantitative research was elaborated. The population constituted the main types of Investment and its Features demostrados in Folha de São Paulo. The study ’s sample consisted of random way. The period to be analyzed , was the year 2010.In the study we used the investments available in the financial market and able to be profitable and callable in the short term, considering the initial value of R 100,000.00. To analyze the data, we applied the technique of descriptive statistics. The results showed that the most significant profit was the dollar, gold and the NTN-B. But the high, medium and low-risk, respectively, need to be assessed in addition to the profits. The income tax and the administrative fees reduced the recommended investments from 12 to 6. Stressing that for its high risk the dollar ceases to be a viable option for the value and period considered. Despite the high value of the tax and medium risk, gold reached the highest profitability and liquidity and remained the most appropriate investment.